Efficacy and safety of zoledronic acid in the treatment of osteoporosis: A meta-analysis of randomized controlled trials - Jianfeng Sun; Masoud Rahmati; Wenqing Xie; Guang Yang; Bingzhou Ji; Dong Keon Yon; Seung Won Lee; Razak M. Gyasi; Guillermo F. López Sánchez; Pinar Soysal; Ai Koyanagi; Lee Smith; et al. (Heliyon, 2024)
Purpose: Zoledronic acid can inhibit the activity of osteoclasts, and thus, may slow or inhibit bone loss. The purpose of this study was to systematically evaluate the efficacy and safety of zoledronic acid in the treatment of osteoporosis. Methods: Four databases, PubMed, Embase, Cochrane Library, and Web of Science, were systematically searched up to December 26, 2022. The primary outcomes included bone mineral density (BMD), carboxy-terminal cross-linked telopeptide of type 1 collagen (CTX), bone-specific alkaline phosphatase (BSAP), procollagen type 1 N-terminal prope-ptide (P1NP), adverse events, and fracture. Secondary outcomes included serum sclerostin level, Visual Analogue Scale (VAS) score, and Oswestry Disability Index (ODI). Results: A total of 22 randomized controlled trials were included in this meta-analysis. Meta-analysis results showed that zoledronic acid was effective in increasing BMD of the lumbar spine, femoral neck, trochanter and serum sclerostin level; and reduced CTX, BSAP, P1NP, VAS score, and ODI in patients with osteoporosis. Regarding safety, zoledronic acid could reduce the incidence of fractures but had relatively more adverse events. Conclusion: Zoledronic acid can significantly improve BMD of the lumbar spine, femoral neck and trochanter, and effectively reduce incidence of fracture in patients with osteoporosis, thereby significantly improving patients' quality of life. However, the incidence of adverse events was higher than that of patients treated with placebo.